2019
DOI: 10.1108/apjml-04-2019-0247
|View full text |Cite
|
Sign up to set email alerts
|

Young consumers’ brain responses to pop music on Youtube

Abstract: Purpose The purpose of this paper is to determine the auditory-sensory characteristics of the digital pop music that is particularly successful on the YouTube website by measuring young listeners’ brain responses to highly successful pop music noninvasively. Design/methodology/approach The authors conducted a functional near-infrared spectroscopy (fNIRS) experiment with 56 young adults (23 females; mean age 24 years) with normal vision and hearing and no record of neurological disease. The authors calculated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…Consistent with the views of Cha et al (2019), Wongtadat (2019) states that due to financial, technical, and experimental design constraints, the subjects must meet specific requirements in order to avoid factors other than the expected stimuli that may cause a bias in neural responses. Studies using neuroscience imaging techniques tend to use fewer research participants and also limit the age of participants; that is, the number of participants should be between 12 and 44, and participants’ age should be between 18 and 43 years old.…”
Section: Methodsmentioning
confidence: 94%
“…Consistent with the views of Cha et al (2019), Wongtadat (2019) states that due to financial, technical, and experimental design constraints, the subjects must meet specific requirements in order to avoid factors other than the expected stimuli that may cause a bias in neural responses. Studies using neuroscience imaging techniques tend to use fewer research participants and also limit the age of participants; that is, the number of participants should be between 12 and 44, and participants’ age should be between 18 and 43 years old.…”
Section: Methodsmentioning
confidence: 94%
“…Most of the consumer neuroscience research using fNIRS focussed on the identification of neural correlates associated with merchandising in virtual in-store settings (Krampe et al, 2018b;Liu et al, 2018) or used fNIRS measurements to predict individual food-choice behaviour (Çakir et al, 2018). A recent fNIRS study conducted by Cha et al (2019) correlated neural activation patterns of the mPFC to online popularity of pop music on YouTube, presenting an extension of earlier studies that predicted music popularity in the field of consumer neuroscience applying fMRI (Berns and Moore, 2012). Overall, prior fNIRS research suggested that especially cortical regions are measurable, whilst brain regions located FIGURE 3 | Schematic representation of a trial in the experimental task.…”
Section: Fnirs Data Collectionmentioning
confidence: 93%
“…Plassmann et al (2007) explored, for example, how neuropsychological methods could be used to investigate brand equity as a determining factor that influences the perception and, consequently, the behaviour of consumers. Subsequently, multiple studies demonstrated the predictive power of neuropsychological data, displaying the capability of forecasting music and movie success or advertising elasticities of television ads (Baldo et al, 2015a;Boksem and Smidts, 2015;Venkatraman et al, 2015;Cha et al, 2019;Tong et al, 2020). Although the predictive power of neuropsychological methods has been demonstrated to outperform 'traditional' marketing methods (Venkatraman et al, 2015), neuropsychological methods and the generated neuropsychological insights are only partially adapted in practice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We find that almost 45% of the studies (61 studies) investigate the impact of advertising on consumer behavior (e.g., preferences, satisfaction), emotions (e.g., positive, negative), and cognitive processes (e.g., attention, memory, engagement). Consumer neuroscience research analyses how consumers experience, process and assess advertisements (Astolfi et al, 2008 ; Ohme et al, 2010 ; Treleaven-Hassard et al, 2010 ; Morillo et al, 2015 ; Soria Morillo et al, 2016 ; Cha et al, 2019 ; Golnar-Nik et al, 2019 ; Kaklauskas et al, 2019 ; Kumar et al, 2019 ; Mahamad et al, 2019 ; Shaari et al, 2019 ). Studies focus on all types of advertising, i.e., brochure, billboard advertising, endorsements by spokespersons, movie trailers, television advertisement, social advertisement, Youtube videos and websites (Ohme and Matukin, 2012 ; Vecchiato et al, 2012a , b ; Randolph and Pierquet, 2015 ; Hamelin et al, 2017 ; Jin et al, 2017 ; Missaglia et al, 2017 ; Kong et al, 2019 ).…”
Section: Main Applications In Marketingmentioning
confidence: 99%